Reproducing the virus‐to‐copepod link in Arctic mesocosms using host fitness optimization. Issue Volume 66:Issue S1(2021) Supplement (26th June 2020) - Thingstad, T. Frede; Våge, Selina; Bratbak, Gunnar; Egge, Jorun; Larsen, Aud; Nejstgaard, Jens Christian; Sandaa, Ruth‐Anne
Abstract: By shunting material out of the predatory pathway toward detritus and dissolved material, viruses are believed to have an important impact on biogeochemical functions of the pelagic microbial food web. To include viruses as a single plankton functional type (PFT) in dynamic food web models is, however, not trivial since they will then compete with predators for the same host/prey community as a shared limiting resource. As recently shown, one can solve this problem by introducing adaptation in the defensive and competitive traits of the host (prey) community. We here show how this can reproduce central aspects of viral dynamics as observed in a set of Arctic mesocosm experiments. In these experiments, contrasting microbial trophodynamics have previously been linked to the trophic cascades generated by seasonal vertical migration of large Arctic copepods. This approach thus produces a quantitative theory for the mechanisms regulating virus‐to‐prokaryote and lysis‐to‐predation ratios, and integrates this with a central role of predator top‐down control in pelagic microbial food webs.